Effects of amyloid beta peptide on neurovascular cells - Askarova, Sholpan; Tsoy, Andrey; Shalakhmetova, Tamara; Lee, James C-M. (Central Asian Journal of Global Health, 2012)
Alzheimer’s disease (AD) is a chronic neurodegenerative disorder, which is characterized by the accumulation of amyloid plaques and neurofibrillary tangles in specific regions of the brain, accompanied by impairment of the neurons, and progressive deterioration of cognition and memory of affected individuals. Although the cause and progression of AD are still not well understood, the amyloid hypothesis is dominant and widely accepted. According to this hypothesis, an increased deposition of amyloid-β peptide (Aβ) in the brain is the main cause of the AD’s onset and progression. There is increasing body of evidence that blood-brain barrier (BBB) dysfunction plays an important role in the development of AD, and may even precede neuron degeneration in AD brain. In the early stage of AD, microvasculature deficiencies, inflammatory reactions, surrounding the cerebral vasculature and endothelial dysfunctions are commonly observed. Continuous neurovascular degeneration and accumulation of Aβ on blood vessels resulting in cerebral amyloid angiopathy is associated with further progression of the disease and cognitive decline. However, little is known about molecular mechanisms that underlie Aβ induced damage of neurovascular cells. In this regards, this review is aimed to address how Aβ impacts the cerebral endothelium. Understanding the cellular pathways triggered by Aβ leading to alterations in cerebral endothelial cells structure and functions would provide insights into the mechanism of BBB dysfunction and inflammatory processes in Alzheimer’s, and may offer new approaches for prevention and treatment strategies for AD.
Keywords: amyloid-beta petide; Alzheimer’s disease; Research Subject Categories::MEDICINE; Research Subject Categories::MEDICINE::Microbiology, immunology, infectious diseases